The Ethnomedicine Study of Muscle Flour Herbal (Borreria Laevis) In The Tengger Tribe of Bromo East Java as Anti-Inflamation - Rony Setianto; Hasanuddin, Asni; Jurnal Syarif (PT Inovasi Pratama Internasional, 2022)
Objective: Local wisdom, especially in the ethnomedicine of the Tengger Bromo tribe, East Java, makes a potential that must be developed sustainably. Muscle Flour (Borreria laevis) is a plant that has anti-inflammatory potential in the Tengger tribe. This plant has high ICF and UV tilapia. Methods: This study aims to determine the types of plants that have been used by the Tengger tribe that have anti-inflammatory activity with the in vitro method of cell membrane stability. Samples were taken from the Tengger Bromo Probolinggo Tribe and extracted by maceration using 95% ethanol. Characterization includes non-specific parameters and specific parameters. Results: Identification of chemical contents includes flavonoids, glycosides, saponins, and alkaloids. Testing of anti-inflammatory activity using ethanol extract from muscle flour made concentrations of 250 ppm, 500 ppm, 1000 ppm, and 2000 ppm with the in vitro anti-inflammatory test with the human red blood cell (HRBC) method or cell membrane stability. Subsequently tested in vivo with the carrageenan induction method 0.1 mg kg / BW rats, positive control methylprednisolone 0.072 mg/kg BW rats, at a dose of selected plant extracts 105 mg kg / BW rats, 210 mg kg / BW rats, and 560 mg kg / BB mouse.